Implementasi Model PBL untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Matematika di SDN Medaeng 2 Sidoarjo - Emilia Emilia; Putri Rachmadyanti; Fadjarwati Fadjarwati (Journal on Education, 2023)
The purpose of this study was to improve student learning outcomes in Mathematics in the material for adding numbers for Grade 1 (one) students through the application of a project based learning model at SDN Medaeng 2 Sidoarjo Regency for the 2022/2023 academic year. The research design is class-based action research (CAR). The research consisted of two cycles with planning, action, observation, and reflection stages. The focus of the research was the teachers and students in class I (one) of SDN Medaeng 2 Sidoarjo totaling 23 students with details of 12 students being boys and 11 students being girls. Data collection techniques consist of observation techniques, learning achievement tests, and field notes when learning activities take place. The conclusion of the research results shows that the implementation of the Project Based Learning (PBL) model can improve student learning outcomes from Pre-cycle to Cycle I and to Cycle II in the activities of teachers, students, and students' Mathematics learning outcomes with a pre-cycle percentage of 34.7%. the average value is 55 then the first cycle increases by 69.56% the average value is 67.17 and increases again in the results of the implementation of the second cycle to 91.3% the average value is 80.43. Based on these result data by applying Problem Based Learning (PBL) addition material can improve the Mathematics learning outcomes of class I (one) SDN Medaeng 2 Sidoarjo and present a fun learning atmosphere and inspire students to be actively involved in learning.